MERITS AND DEMERITS OF DESIGNING HOT-POTATOES MATERIALS FOR EFL LEARNERS - Lini Fitri; Gatot Sutapa; Sudarsono Sudarsono (ICoTE Proceedings, 2018)
Teaching materials are needed in teaching-learning activities in the classroom because materials have been considered as the only way to supply enriched input in the language classroom. Nowadays, technology has had a major impact, especially on education. Application of Information and Communication Technology (ICT), particularly educational software, to facilitate the learning and teaching process has become a more and more popular trend among teachers. The aim of this article is to explore the merits and demerits designing of Hot Potatoes as teaching material in the classroom in order to motivate EFL learners in learning simple past tense towards the interactive exercises. Hot Potatoes is popular software which can be conveniently used to create interactive Web-based educational exercises. Some of the advantages of hot-potatoes are: Enable teachers to create small exercises to practice and it can be linked to a listening or reading text to make a complete comprehension exercise.